SOSIALISASI HIDUP SEHAT SEJAK DINI : EDUKASI ISI PIRINGKU BAGI SISWA KELAS V SD YAYASAN PRAYOGA PADANG - Reny Salim; Tuty Taslim; Verawaty Verawaty; Irene Puspa Dewi; Fita Selonni (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2023)
Many children or adolescents still suffer from imbalances in nutritional intake. The Indonesian government, in particular, has created an educational program, "Isi Piringku", to restore the Indonesian people's nutritional intake. One form of government effort is the existence of teaching materials about healthy food for grade 5 elementary school students. This service aims to educate grade 5 elementary school students on "Fill My Plate". The method used in the implementation of this educational service is reflective thinking. The results obtained from this activity were that elementary school students had fairly good basic knowledge regarding healthy types of food but did not know that knowledge was a guideline the government had recommended with the theme of the contents of my plate. Balanced nutrition education activities must be carried out continuously at all levels of society.